2020
DOI: 10.1101/2020.08.13.249979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial Vipp1 and PspA are members of the ancient ESCRT-III membrane-remodelling superfamily

Abstract: Membrane remodelling and repair are essential for all cells. Proteins that perform these functions include Vipp1/IM30 in photosynthetic plastids, PspA in bacteria, CdvB in TACK archaea and ESCRT-III in eukaryotes. Here, we show that these protein families are homologous and share a common evolutionary origin. Using cryo-electron microscopy we present structures for Vipp1 rings over a range of symmetries. Each ring is built from rungs that stack and spontaneously self-organise to form domes. Rungs are assembled… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 70 publications
(69 reference statements)
3
19
0
Order By: Relevance
“…While this study establishes that PspA is a member of the ESCRT-III family, this membership has now been confirmed for PspA related bacterial IM30/Vipp1 proteins by two independent studies: first, derived from bioinformatic analysis and followed by single-particle cryo-EM of IM30/Vipp1 rings revealed a conserved ESCRT-III fold (Liu et al, 2020). Second, the cryo-EM single-particle structure of IM30/Vipp1 rings as well as in situ cryo-EM studies revealed the presence of Vipp1 rods in Chlamydomonas reinhardtii (Gupta et al, 2020).…”
Section: Limitations Of the Studysupporting
confidence: 55%
“…While this study establishes that PspA is a member of the ESCRT-III family, this membership has now been confirmed for PspA related bacterial IM30/Vipp1 proteins by two independent studies: first, derived from bioinformatic analysis and followed by single-particle cryo-EM of IM30/Vipp1 rings revealed a conserved ESCRT-III fold (Liu et al, 2020). Second, the cryo-EM single-particle structure of IM30/Vipp1 rings as well as in situ cryo-EM studies revealed the presence of Vipp1 rods in Chlamydomonas reinhardtii (Gupta et al, 2020).…”
Section: Limitations Of the Studysupporting
confidence: 55%
“…We used these analyses to explore and identify novel components of the Psp stress response system. We first established that PspA/Snf7 is universal and that the ancestry of the PspA/Snf7 superfamily traces back to the last universal common ancestor (LUCA), in agreement with a recent study [10]. A corollary to this finding is that, despite the different types of membranes ( e.g., ether-linked vs. ester-linked) in the archaeal, bacterial, and eukaryotic lineages, the LUCA already possessed a membrane whose curvature and dynamics were mediated by an ancestral PspA/Snf7-like coiled-coil protein assembled into polymeric structures adjacent to the inner-leaf of the membrane.…”
Section: Discussionsupporting
confidence: 89%
“…Since membrane damage can ultimately result in cell death, a specialized suite of lipids and proteins participate in sensing and responding to this stress [8,9], initiating a chain of events to restore membrane function. Among the mechanisms involved in maintaining the biophysical properties of the cell membrane is the ESCRT system in eukaryotes and the Phage Shock Protein (PSP) system in bacteria [2,1013]. The multi-protein PSP system constitutes a ubiquitous envelope stress response machinery found across bacterial phyla that comprises both conserved and lineage-specific components expressing conserved stress response functions [1,2,10,11,1316,1621].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, such polymer flexibility would open the possibility of adapting to a wide range of diverse curvatures, including highly curved filaments, by the same polymer as well as accumulating elastic energy within the filaments (Figure 1C). In support of this, the recent structures of the plastid and bacterial homologs of ESCRT-III called Vipp1 (vesicle inducing protein in plastids 1, also named IM30) and PspA, respectively, show that many intermediates from semi-open to fully open conformations can polymerize in rings of different curvatures [17][18][19]. By contrast, the head-to-tail arrangement of the closed conformation displays much less intersubunit contacts and can be assumed to result in a more rigid filament, which is less resistant to torsional stress (Figure 1B).…”
Section: Open Accessmentioning
confidence: 89%